2021
DOI: 10.1590/1516-4446-2019-0803
|View full text |Cite
|
Sign up to set email alerts
|

Association between poor tolerability of antidepressant treatment and brain functional activation in youth at risk for bipolar disorder

Abstract: Objective: To investigate whether poor antidepressant tolerability is associated with functional brain changes in children and adolescents of parents with bipolar I disorder (at-risk youth). Methods: Seventy-three at-risk youth (ages 9-20 years old) who participated in a prospective study and had an available baseline functional magnetic resonance imaging (fMRI) scan were included. Research records were reviewed for the incidence of adverse reactions related to antidepressant exposure during follow-up. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These adverse effects can also manifest as poor tolerability in youth at risk for bipolar disorder, as evidenced by decreased right amygdala activation in response to emotional distracters. In addition to the physical manifestations of ADRs, the impact of antidepressants on mental health and behavior is also a significant concern (Nery et al, 2021). For instance, decreased right amygdala activation in response to emotional distracters has been associated with experiencing antidepressant-related adverse reactions in at-risk youth, highlighting the potential impact on brain functional activation (Nery et al, 2021).…”
Section: Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These adverse effects can also manifest as poor tolerability in youth at risk for bipolar disorder, as evidenced by decreased right amygdala activation in response to emotional distracters. In addition to the physical manifestations of ADRs, the impact of antidepressants on mental health and behavior is also a significant concern (Nery et al, 2021). For instance, decreased right amygdala activation in response to emotional distracters has been associated with experiencing antidepressant-related adverse reactions in at-risk youth, highlighting the potential impact on brain functional activation (Nery et al, 2021).…”
Section: Antidepressantsmentioning
confidence: 99%
“…In addition to the physical manifestations of ADRs, the impact of antidepressants on mental health and behavior is also a significant concern (Nery et al, 2021). For instance, decreased right amygdala activation in response to emotional distracters has been associated with experiencing antidepressant-related adverse reactions in at-risk youth, highlighting the potential impact on brain functional activation (Nery et al, 2021). Additionally, Williams et al (2015) suggested that amygdala reactivity to emotional faces may help predict general and medication-specific responses to antidepressant treatment, indicating the potential of amygdala probes in informing the personal selection of antidepressant treatments.…”
Section: Antidepressantsmentioning
confidence: 99%
“…In contrast, one study identified a significant difference in mean activation in the right amygdala among youth with a familial risk for bipolar disorder treated with antidepressants, at-risk youth without antidepressant use, and healthy controls. Specifically, youth at risk for bipolar disorder who were treated with antidepressants and experienced an antidepressant-related adverse reaction had the lowest amygdala activation at baseline [ 50 ]. These findings suggest that in youth at risk for bipolar disorder, baseline dysregulation of amygdala activity may be exacerbated by antidepressants and inadequately moderated by prefrontal regulation of amygdala activity, leading to adverse behavioral reactions such as aggression, impulsivity, and irritability [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, youth at risk for bipolar disorder who were treated with antidepressants and experienced an antidepressant-related adverse reaction had the lowest amygdala activation at baseline [ 50 ]. These findings suggest that in youth at risk for bipolar disorder, baseline dysregulation of amygdala activity may be exacerbated by antidepressants and inadequately moderated by prefrontal regulation of amygdala activity, leading to adverse behavioral reactions such as aggression, impulsivity, and irritability [ 50 ]. Though replicable findings describe consistent patterns of neural activity and modulation, antidepressants may exert dynamic effects on the brain which require repeated assessment over time.…”
Section: Introductionmentioning
confidence: 99%